Therapeutic Effects of "Ibuprofen, Diphenhydramine and Aluminium MgS" on Recurrent Aphthous Stomatitis: A Randomized Controlled Trial. - Katayoun Borhan-Mojabi; Faezeh Mirmiran; Marjan Nassiri-Asl; Pantea Nazeman; Hassan Jahanihashemi (Tehran University of Medical Sciences, 2014)
Recurrent aphthous stomatitis (RAS) is the most common and painful oral inflammatory lesion with an unknown etiology. This study aims to determine the therapeutic effects of ibuprofen, diphenhydramine and aluminum magnesium simethicone (AlMgS) syrup on reducing oral aphthous ulcer pain.Thirty-one patients with RAS participated in this double-blind clinical trial. Subjects were randomly divided into two groups. The control group (n=14) received drug mixture as drug A (diphenhydramine and AlMgS) and the case group (n=17) received drug B (ibuprofen, diphenhydramine and AlMgS). Drugs were topically applied on ulcers by the patients three times a day for 3 days. Patients were re-examined for the symptoms on the fourth day following their first visits using VAS (Visual Analogue Scale) tool. Statistical analysis was performed using paired t-test, independent t-test and chi-square test.The mean of pain reduction was 3.17±2 (P